Claustrum damage and refractory status epilepticus following febrile illness - Meletti, Stefano; Slonkova, Jana; Mareckova, Iva; Monti, Giulia; Specchio, Nicola; Hon, Petr; Giovannini, Giada; Marcian, Vaclav; Chiari, Annalisa; Krupa, Petr; Pietrafusa, Nicola; Fiedorová, Dagmar; et al. (Neurology, 2015)
OBJECTIVE: To characterize the clinical, EEG, and brain imaging findings in an adult case series of patients with de novo refractory status epilepticus (SE) occurring after a febrile illness. METHODS: A retrospective study (2010-2013) was undertaken with the following inclusion criteria: (1) previously healthy adults with refractory SE; (2) seizure onset 0-21 days after a febrile illness; (3) lacking evidence of infectious agents in CSF; (4) no history of seizures (febrile or afebrile) or previous or concomitant neurologic disorder. RESULTS: Among 155 refractory SE cases observed in the study period, 6 patients (17-35 years old) fulfilled the inclusion criteria. Confusion and stupor were the most common symptoms at disease onset, followed after a few days by acute repeated seizures that were uncountable in all but one. Seizures consisted of focal motor/myoclonic phenomena with subsequent generalization. Antiepileptic drugs failed in every patient to control seizures, with all participants requiring intensive care unit admission. Barbiturate coma with burst-suppression pattern was applied in 4 out of 6 patients for 5-14 days. One participant died in the acute phase. In each patient, we observed a reversible bilateral claustrum MRI hyperintensity on T2-weighted sequences, without restricted diffusion, time-related with SE. All patients had negative multiple neural antibodies testing. Four out of 5 surviving patients developed chronic epilepsy. CONCLUSIONS: This is a hypothesis-generating study of a preliminary nature supporting the role of the claustrum in postfebrile de novo SE; future prospective studies are needed to delineate the specificity of this condition, its pathogenesis, and the etiology.
Keywords: antikonvulziva; magnetická rezonanční tomografie; Anticonvulsants; Retrospective Studies; Status Epilepticus; poranění mozku; Magnetic Resonance Imaging; lidé; Seizures; Adult; dospělí; Brain Injuries; Female; status epilepticus; Male; ženské pohlaví; mladý dospělý; Humans; mužské pohlaví; záchvaty; Young Adult; bazální ganglia; Electroencephalography; elektroencefalografie; Basal Ganglia; retrospektivní studie